Angiosome～From the Standpoint of Bypass Surgery - Deguchi, Juno (Ann Vasc Dis, 2020)
Although several studies showed that angiosome-guided endovascular treatment improved wound healing and major amputation rates in patients with chronic limb-threatening ischemia (CLTI), effectiveness of the angiosome concept to the treatment of ischemic foot remains to be elucidated, especially in bypass surgery. Arterial anatomy of the foot and ankle shows that there are multiple supplementary circulation including arterial–arterial connections and choke nexus, which indicates angiosome concept may carry limited importance in bypass surgery for CLTI. On the other hand, patients with diabetes or renal dysfunction have partial occlusion of arterial–arterial connections and, therefore, quite a few patients with CLTI in Japan may present with limited but impaired supplementary circulation around the ankle. This article reviews the arterial anatomy and circulation of the foot and ankle and discusses availability and limitations of angiosome-guided bypass surgery.